2015
DOI: 10.2217/fvl.15.43
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T-Cell Response to Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infection and hospitalization among infants. Despite the significant healthcare burden, there is no licensed RSV vaccine currently available. This problem is further exacerbated as a natural RSV infection fails to elicit the development of long-lived immunity. It is well established that RSV-specific antibodies play a critical role in mediating protection from severe disease. The CD8 T-cell response is critical for mediating viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 150 publications
(187 reference statements)
1
2
0
Order By: Relevance
“…Following RSV infection, antigen-specific CD8 T cells exhibit an activated phenotype and gain effector functions 41 corroborating the common theory that inflammatory responses increase with antigen encounters 40 . Notably, in humans, an increase in TEM population can be seen following resolution of infection 44 .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Following RSV infection, antigen-specific CD8 T cells exhibit an activated phenotype and gain effector functions 41 corroborating the common theory that inflammatory responses increase with antigen encounters 40 . Notably, in humans, an increase in TEM population can be seen following resolution of infection 44 .…”
Section: Resultssupporting
confidence: 73%
“…Over time following infection or vaccination, as the antigen load decreases, the population of mature CD8 T cells contracts to form a stable memory CD8 T cell pool whose functional activities evolve with time 40 . As is the role of immune memory, RSV-specific CD8 T cells expand in magnitude and effector functions following infection 41 . However, FIRSV has been shown to elicit no memory CD8 T cell response in mice adding another facet to its ineffectiveness 42 , 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the engagement of PD-1 with inflammatory DC-derived PD-L1 is crucial for regulation of pro-inflammatory cytokine release by effector CD4 and CD8 T cells, resulting in control of effector T cell activities in the lungs. In addition, they showed that blocking PD-L1 following RSV infection enhanced weight loss and lung histopathology in mice 22,59 . Taken together, our observations are in good agreement with severe RSV infection in the murine model where low levels of PD-1 induction accompany enhanced respiratory disease.…”
Section: Discussionmentioning
confidence: 99%